PL.27 Assessment of the Delivery of Cell Penetrating Peptides to Human Uteroplacental Cells. (26th April 2013) - Gurney, LRI; Sweeney, M; Jones, A; Robson, S; Taggart, M
Abstract : Introduction: The increasing incidence of preterm birth, the severity of its consequences and the inability of current therapies to improve morbidity and mortality in clinical trials creates an urgent need to develop effective new treatments 1 . Cell penetrating peptides (CPP's) are short peptides that facilitate delivery of drug cargo across plasma membranes, showing great promise as intracellular drug delivery vectors in many clinical fields 2 . However, the efficacy of CPP delivery of cargo to human uteroplacental cells remains to be resolved. We aimed to explore the capacity of 3 different CPPs to deliver fluorescent cargo to human myometrial and placental cells in vitro. Methods: Human myometrial and amnion cell cultures were prepared from tissues obtained at elective Caesarean section. Three separate CPPs (TAT peptide, polyarginine, and Penetratin peptide) were conjugated to AlexaFLuor488 dye and compared with non-cell-permeable peptide ((GC)4). Cells were incubated at 37°C with fluorescently labelled CPP-cargo conjugates and visualised using live cell confocal microscopy. Results: Myometrial or amnion-derived cells consistently expressed fluorescent cargo delivered with each CPP at 1–10 mM after 1–4 hours. Peptide staining often was punctuate throughout the cell cytoplasm appearing perinuclear at the longest timepoints and highest concentrations. At concentrations below 1 µM there was little evidence of cargo uptake. No fluorescent cargo was delivered with (GC)4. Conclusion: CPP's show promise as cargo delivery vectors in human uteroplacental cells. Their potential use as vectors for bioactive cargo in these cells requires further study. References: Goldenberg et al. Epidemiology and causes of preterm birth. Lancet 2008;372: 75–84. Orange & May. Cell penetrating peptide inhibitors of nuclear factor-kappa B. Mol. Life Sci 2008;65:3564–3591.